ANALISIS YURIDIS PENGATURAN JANGKA WAKTU PENYERAHAN SURAT PEMBERITAHUAN DIMULAINYA PENYIDIKAN OLEH PENYIDIK KEPADA KEJAKSAAN UNTUK MEMULAI PENYIDIKAN BERDASARKAN KITAB UNDANG-UNDANG HUKUM ACARA PIDANA - Brando Pardede; Mexsasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Implementation of the principles contained in the quick coordination between law enforcement agencies, one of which is an investigator with the prosecutor in the case of submission of the Notice of Commencement of Investigation hereinafter abbreviated SPDP, by the investigator to the prosecutor to initiate an investigation. Fast, should be interpreted as a strategic attempt to make the justice system as an institution that can ensure the accomplishment / achievement of justice in law enforcement quickly litigants. Not only quickly resolved origin are applied but juridical considerations, accuracy, precision, and considerations that guarantee sosilogis sense of justice was also considered. SPDP stipulated in Article 109 paragraph (1) Criminal Code, namely: "In the event that investigators have begun an investigation of an event that is a crime, investigators notify the public prosecutor". Period setting SPDP not support fast principle in the criminal justice system in Indonesia. SPDP time period setting is not firm and does not provide legal certainty to cause adverse effects in law enforcement. The purpose of this thesis are: First, to determine whether the arrangement period of submission of the notification the commencement of an investigation by the investigator to the prosecutor's office has supported the principle of fast in the criminal justice system of Indonesia, the Second, to determine the ideal setting of the period for the submission of the notification the commencement of an investigation by investigators to the prosecutor. This research is a normative legal research or can be also called the doctrinal legal research. From the research problem there are two main things that concluded, first, setting a period of submission of SPDP by the investigator to the prosecutor stipulated in Article 109 paragraph (1) Criminal Procedure Code does not yet support fast principle in the criminal justice system in Indonesia. Second, the ideal setting on delivery time SPDP by the investigator to the prosecutor that should be mentioned explicitly in the Criminal Procedure Code.Keywords: Setting Period-Notice of Commencement of Investigation-Quick Principles-The Criminal Justice System